Impact of Facilitator as Simulated patient on Students in Problem Based Learning - Attyia Rashid, Ahsan Sethi, Hussain Ahmad Khaqan, Hasnain Muhammad Buksh, Laraib, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To explore the impact on students (in terms of engagement, improvement in achieving the learning outcomes, motivation and metacognition of prior knowledge) if facilitator behaves as simulated patient in PBL. Methods: The research was carried out at the University College of Medicine and Dentistry in Lahore, Pakistan. The method employed was purposeful heterogeneous sampling. Through an online session of focus group discussion using Zoom software, qualitative data was collected from 30 students and 6 facilitators. The data was transcribed, and the codes were manually coded by highlighting them. Themes were then created Result: Over all, the attitude of students towards simulated PBL was positive and respondents were satisfied. Five emerging themes that supports the efficacy of simulated PBL and active role of facilitators were as follows: PBL is efficacious pedagogy, professional development, life-long learner, impact of role modelling and role of simulation in PBL. Conclusion: The study concludes that PBL is an effective pedagogy, the role of facilitators’ impacts positively on students by enhancing their professional development like communication skills, empathy and confidence. Simulation and role modelling by the facilitator inculcate the confidence and competence and make them lifelong learner. Key words: Engagement, Facilitator, Problem based learning, Qualitative, Simulation